2005
DOI: 10.1021/je049559v
|View full text |Cite
|
Sign up to set email alerts
|

Density and Viscosity of Saturated Liquid Dimethoxymethane from (218.15 to 383.15) K

Abstract: The density and viscosity of saturated liquid dimethoxymethane were measured over the temperature range from (218.15 to 383.15) K with a vibrating-tube densimeter and a calibrated Ubbelohde-type capillary viscometer, respectively. The estimated uncertainties of the measurements were ±1.0 kg/m3 for density and ±1.8% for viscosity. Density results were fitted using the polynomial with an absolute average deviation of 0.13% and a maximum deviation of 0.22% from the correlated equation. Viscosity results were corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…From the plot in Fig. 3, it is observed that the present measurements agree with our previous results [5] very well over the temperature range from 263.07 K to 383.16 K, with a maximum deviation of −1.59 %. But at temperatures from 243.14 K to 258.12 K, larger deviations of −4.31 % to −10.06 % were observed.…”
Section: Dimethoxymethanesupporting
confidence: 90%
See 3 more Smart Citations
“…From the plot in Fig. 3, it is observed that the present measurements agree with our previous results [5] very well over the temperature range from 263.07 K to 383.16 K, with a maximum deviation of −1.59 %. But at temperatures from 243.14 K to 258.12 K, larger deviations of −4.31 % to −10.06 % were observed.…”
Section: Dimethoxymethanesupporting
confidence: 90%
“…Francesconi and Comelli [19] reported measurements at 288.15 K and 298.15 K, with deviations of −0.39 % and −0.73 % from the correlation. For the purpose of comparison with our previous work [5], obtained with the vibrating-tube densimeter, the small extrapolations of the present data to the saturation line were performed, and the vapor pressures were from Pan et al [8]. The differences vary from −0.60 % at 233.16 K to 0.95 % at 363.11 K. The viscosity deviations for dimethoxymethane between this work and literature results are shown in Fig.…”
Section: Dimethoxymethanesupporting
confidence: 55%
See 2 more Smart Citations
“…Complex formation in liquid mixtures has been extensively studied using optical and ultrasonic technique by many workers [1][2][3]. The formation of hydrogen bond in solutions and its effect on the physical properties of the mixtures have received much attention.…”
Section: Introductionmentioning
confidence: 99%